Tindak Tutur Komisif pada Baliho Calon Wali Kota dan Wakil Wali Kota Ternate Tahun 2020 - Sasmayunita (GERAM: Gerakan Aktif Menulis, 2021)
This study examines the problem of commissive speech acts in candidates for mayor and deputy mayor of Ternate in 2020. The purpose of this study is to describe the form of commissive speech acts on billboards for candidates for mayor and deputy mayor of Ternate in 2020. This type of research is descriptive qualitative. The data source is the discourse on the billboards for the 2020 Mayor and Deputy Mayor of Ternate. The technique of collecting is through observation, documentation, and taking notes. The data analysis technique in this study is the content analysis method by examining all data from various sources according to observations, documentation, and listening results (notes). Next, sort, analyze, and describe the forms of commissive speech acts and conclude the findings. The findings show several forms of commissive speech acts: commissive speech acts of intention, promise, and commissive speech acts of offering. This study recommends that further researchers conduct studies on different objects with a broader amount of data.